Evaluate The Skill Level in Playing Basic Techniques Women's Extracurricular Participant Volleyball at Junior High School 8 Lawe Sigala-Gala - Tahir, Muhammad (Indonesian Research Journal on Education, 2024)
The game of volleyball is not only for recreational facilities or to fill free time but also develops towards competition and achievement to achieve achievements, so football players need to master the basic techniques of playing football, namely passing, service, and smash. If volleyball players can master the basic techniques of volleyball, their skills in playing volleyball will also increase so that they can achieve good achievements. The purpose of this study is to evaluate the volleyball playing skills of female volleyball extracurricular participants at SMP Negeri 8 Lawe Sigala-gala. The results of this study can be used as a reference for women's volleyball extracurricular coaches to find out how much they master the basic football techniques. In addition, it is also to find out the extent of the playing skills of women's volleyball participants when facing opponents. Furthermore, to develop the right training program for extracurricular participants. This research is a quantitative research because the data produced is in the form of numbers. The results of the study showed that the basic technique of playing volleyball for girls extracurricular volleyball participants at SMP Negeri 8 Lawe Sigala-gala was 72% or 10 out of 14 students. then for the playing skills measured by VIS showing that better than the opposing team is proven by winning 2 sets at once.